PENGARUH PENETAPAN HARGA PRODUK TERHADAP LOYALITAS PELANGGAN STUDI KASUS PADA PUSAT GROSIR BANDUNG: PENGARUH PENETAPAN HARGA PRODUK TERHADAP LOYALITAS PELANGGAN STUDI KASUS PADA PUSAT GROSIR BANDUNG - sugiat, jajang; Rusdian, Suca; Maryani, Yuni (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Customer loyalty needs to understand the buying cycle. The purchase cycle starts from the consumer making a purchase for the first time then the consumer will conduct a post-purchase evaluation on the product, after which the consumer will decide to buy the product again or not. This research is stated in the hypothesis that there is a positive influence between pricing on customer loyalty (Study at Bandung Wholesale Center). The population in this study are customers who make purchases at the Bandung Wholesale Center which are unlimited (infinite). In determining the number of samples will be used based on the calculation of the Lamshow formula. Then the size of the sample based on the number of populations who buy products at the Bandung Wholesale Center is the result of calculations obtained by the value of n = 68, the number of respondents studied is 68 people. Based on the results of calculations using Pearson Product Moment correlation coefficient analysis partially Product Pricing (X) has an effect on Customer Loyalty (Y) can be obtained the result is 0.855 which indicates a very strong influence between Product Pricing and Customer Loyalty. The correlation value which is between 0.800-1000 is in a strong interval, so it can be said that Product Pricing is a priority role for Customer Loyalty.